Tekanan Anggaran Waktu Memoderasi Pengaruh Role Stres Terhadap Perilaku Disfungsional Auditor - Limbong, Christine Octo Debora; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2020)
The purpose of this study is to analyze the time budget pressure moderate the influence of the role of stress on the auditor's dysfunctional behavior (Study at PT Bank BNI Denpasar Regional Office). This research was conducted in all thirty-two offices of PT Bank BNI Denpasar Regional Officein the Bali Region in 2019 by making 68 auditors as samples using the saturated sample method. Data collection is done by distributing questionnaires, tested through regression analysis moderation (MRA) techniques. Based on the analysis, the role stress variable has a significant positive effect on the dysfunctional behavior of auditors at PT Bank BNI Denpasar Regional Office. Time budget pressure has a significant positive effect on the auditor's dysfunctional behavior at PT Bank BNI Denpasar Regional Office. Time budget pressure moderates the influence of role stress on the auditor's dysfunctional behavior at PT Bank BNI Denpasar Regional Office. Keywords: Role Stress; Time Budget Pressure; Auditor's Dysfunctional Behavior.